TIMM23 overexpression drives NSCLC cell growth and survival by enhancing mitochondrial function - Jianhua Zha; Jiaxin Li; Hui Yin; Mingjing Shen; Yingchen Xia (Cell Death and Disease)
Abstract Mitochondrial hyperfunction is implicated in promoting non-small cell lung cancer (NSCLC) cell growth. TIMM23 (translocase of inner mitochondrial membrane 23) is a core component of the mitochondrial import machinery, facilitating the translocation of proteins across the inner mitochondrial membrane into the matrix. Its expression and potential functions in NSCLC were tested. Comprehensive bioinformatic analysis revealed a strong correlation between TIMM23 overexpression and adverse clinical outcomes in NSCLC patients. Single-cell RNA sequencing data further corroborated these findings, demonstrating elevated TIMM23 expression within the cancer cells of NSCLC mass. Subsequent experimental validation confirmed significantly increased TIMM23 mRNA and protein levels in locally-treated NSCLC tissues compared to matched normal lung tissues. Moreover, TIMM23 expression was consistently elevated across multiple primary/established NSCLC cells. Silencing or ablation of TIMM23 via shRNA or CRISPR/Cas9 in NSCLC cells resulted in impaired mitochondrial function, characterized by reduced complex I activity, ATP depletion, mitochondrial membrane potential dissipation, oxidative stress, and lipid peroxidation. These mitochondrial perturbations coincided with attenuated cell viability, proliferation, and migratory capacity, and concomitant induction of apoptosis. Conversely, ectopic overexpression of TIMM23 significantly enhanced mitochondrial complex I activity and ATP production, promoting NSCLC cell proliferation and motility. In vivo, intratumoral delivery of a TIMM23 shRNA-expressing adeno-associated virus significantly suppressed the growth of subcutaneous NSCLC xenografts in nude mice. Subsequent analysis of tumor tissues revealed depleted TIMM23 expression, ATP reduction, oxidative damage, proliferative arrest, and apoptotic induction. Collectively, these findings establish TIMM23 as a critical pro-tumorigenic factor in NSCLC, highlighting its potential as a prognostic biomarker and therapeutic target.